Flood of fire [compact disc, unabridged] : a novel - Ghosh, Amitav, 1956- (Ibis trilogy, 2015)
Follows Kesri Singh, an East India Company soldier, on his 1839 journey to Hong Kong after the British colonial government assembles an expeditionary force to end a costly embargo on the eve of the Opium Wars.